IKLIM KOMUNIKASI PADA KOMUNITAS TRASHBAG PALU - Desrianita, Dwi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2018)
This research is a qualitative descriptive study. The purpose of this study was to find out how the communication climate took place in the Trashbag community activities. To see how the communication climate in the Trashbag community researchers see using five dimensions of communication climate according to Redding and Goldhaber. Namely Supportiveness or mutual support, participation, trust, openness, and high performance goals. From these five points the researchers also analyzed how the communication process was of two types, namely horizontal communication and vertical communication. In this study, researchers approached participant observation which required researchers to take part in the Sapu Jagad 2017 activity, which is a routine activity held by Trashbag every year. The results of this thesis are Trashbag members who always provide support in terms of decision making and when members will carry out their respective duties. Palu Trashbag members and Jagad Sweep committee also participate voluntarily. Members / volunteers Trashbag put so far have had a sense of trust in each other member but not yet comprehensive. Trashbag is a community that implements a non-binding flexible system so that members can be more open. When all members feel open to each other to achieve the community's vision and mission according to researchers, it can be more maximal.